Supervision work at site (Recreational area in UiTM Seri Iskandar, Perak Darul Ridzuan) / Muhamad Daniesy Zamri - Muhamad Daniesy, Zamri (Universiti Teknologi Mara, Perak, 2017)
This content of report consist of all the information during the internship period. Basically, this report will completely elaborate all the activity and work done. The content of this report will explain about the department, the organization, the work carried out and etc. In specific, all the information about the department will be stated as it is the place for the internship, the project involvement, scope of work, problem and counter measure and etc. For the introduction, the department is Facility Management Dept. In UiTM Seri Iskandar where as the dept were totally in-house dept. The main purpose of the department is to manage all the facility inside campus including civil work maintenance, mechanical and landscape. The department consists of 3 section total of 47 staffs lead by Mrs. Azizah as the head of department. The office located opposite to Real estate department building. Basically they manage all the technical and maintenance work inside UiTM.